2005
DOI: 10.1002/jsfa.2297
|View full text |Cite
|
Sign up to set email alerts
|

Physiological properties of fresh‐cut watermelon (Citrullus lanatus) in response to 1‐methylcyclopropene and post‐processing calcium application

Abstract: Seedless watermelon (Citrullus lanatus Thunb. Mansfeld, cv. Millionaire) fruit were exposed to 10 µL L −1 1-methylcyclopropene (1-MCP) or air for 18 h. Afterward, the fruit were processed into placental-tissue pieces, treated with calcium dips (20 g kg −1 CaCl 2 ) or deionized water, and stored in vented containers for 7 days at 10 • C. At intervals during storage, fresh-cut placental tissue was monitored for respiration, ethylene production, firmness, electrolyte leakage, total soluble solids, titratable acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 51 publications
(52 reference statements)
0
24
1
2
Order By: Relevance
“…The respiration rate of all 5 cultivars decreased gradually and in parallel during the 5 day storage period with the greatest decrease for 8424 seeded ( Table 2). The results of the present study, contradict the findings of other authors (Mao et al [9], Saftner et al [11], Saftner and Lester [24] who reported increases in CO 2 activity in fresh-cut muskmelon and watermelon. The differences between these studies may be attributed to a variety of factors including differences in cultivars, period from cutting to determination, length of storage period and storage temperature as well as the relatively low microbial count of the samples.…”
Section: Respiration Ratecontrasting
confidence: 95%
See 1 more Smart Citation
“…The respiration rate of all 5 cultivars decreased gradually and in parallel during the 5 day storage period with the greatest decrease for 8424 seeded ( Table 2). The results of the present study, contradict the findings of other authors (Mao et al [9], Saftner et al [11], Saftner and Lester [24] who reported increases in CO 2 activity in fresh-cut muskmelon and watermelon. The differences between these studies may be attributed to a variety of factors including differences in cultivars, period from cutting to determination, length of storage period and storage temperature as well as the relatively low microbial count of the samples.…”
Section: Respiration Ratecontrasting
confidence: 95%
“…This has provided the impetus for much research investigating the shelf-life of specific cultivars of fresh-cut watermelon, suppressing microbial growth and maintaining quality [7,8]. Others have reported on the effects of 1-Methylcyclopropene (1-MCP) on metabolism and quality characteristics [9,10,11,12] and on flesh quality and Lycopene stability of fresh-cut watermelon [13]. Evidently, the quality, physio-biochemical and microbial attributes investigated in the literature are important determinants of quality.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, a surface treatment, even if not effective on the whole product, could be sufficient to extend the product shelf life (Artes-Hernandez, Robles, Gomez, TomasCallejas, & Artes, 2010;Manzocco, Da Pieve, & Maifreni, 2011;Saftner, Luo, McEvoy, Abbott, & Vinyard, 2007;Watada, 1990). Similar to other fresh-cut fruits, quality loss of fresh-cut watermelon can be described as loss of texture, color, and sweetness (Mao, Jeong, Que, & Huber, 2006;Perkins-Veazie & Collins, 2004;Rushing, Fonseca, & Keinath, 2001).…”
Section: Introductionmentioning
confidence: 96%
“…This observation suggests that polyuronide solubility and depolymerization in papaya fruit is possibly ethylene independent at the final stages of ripening in papaya fruit or that 1-MCP is ineffective in delaying the changes in polyuronides in fruit that are already ripe or at an advanced ripening stage. This has also been reported for kiwifruit treated with 1-MCP before slicing as well as for fresh-cut pineapple and watermelon (Budu and Joyce 2003;Mao et al 2006). Significant changes were also evident in neutral hemicelluloses and hemicellulosic polysaccharides during storage at 5°C.…”
Section: Discussionmentioning
confidence: 53%